An overview of hepatitis B prevalence, prevention, and management in the Pacific Islands and Territories. Issue 11 (November 2014) - Howell, Jessica; Van Gemert, Caroline; Lemoine, Maud; Thursz, Mark; Hellard, Margaret
Abstract There are over 500–750 000 deaths per year because of hepatitis B virus (HBV)‐related cirrhosis and liver cancer worldwide and the World Health Organization Western Pacific Region has some of the highest endemic levels of HBV in the world, particularly within China, South East Asia and Pacific Island Countries and Territories (PICT). The PICT have unique ethnic diversity and a very high prevalence of smoking and metabolic syndrome, both important risk factors for liver fibrosis and liver cancer. However, in contrast to many Asian countries, there is little published data on HBV prevalence and related liver disease burden in PICT. In this review, the available published literature and World Health Organization data for HBV prevalence and related liver disease and liver cancer burden in PICT is outlined, and unmet needs for improving HBV prevention and control in the region are highlighted.